Case report: DKRd regimen in the treatment of newly diagnosed POEMS syndrome and literature review - Wang, Jianchao; Liao, Wensheng; Liu, Zhongwen; Kong, Dai (Frontiers in Oncology, 2024)
POEMS syndrome, characterized as a rare multisystem paraneoplastic syndrome, arises from plasma cell abnormalities. Coined by Bardwick in 1980, the acronym POEMS delineates the distinctive features of the syndrome: Peripheral nerve Lesions, Organomegaly, Endocrinopathy, Monoclonal gammopathy, and Skin changes. The prevalence of POEMS syndrome stands at approximately 0.3 per 100,000 individuals. Owing to its low prevalence and the paucity of prospective studies, current treatment approaches largely hinge on retrospective studies and revolve around the use of plasma cell-directed therapy typically used in multiple myeloma treatments. This article presents the pioneering case of utilizing a four-drug combination regimen of DKRd (daratumumab, carfilzomib, lenalidomide, and dexamethasone) as a first-line treatment. This is succeeded by induction therapy and subsequently, autologous hematopoietic stem cell transplantation. A comprehensive review of related literature is conducted.